Phase composition of galvanic iron-nickel alloys obtained using pulsed current - Ganich, R.P.; Zabludovsky, V.O.; Artemchuk, V.V.; Zelenko, Y.V.; Markul, R.V. (Physics and Chemistry of Solid State, 2021)
The paper presents the results of studying the phase composition of iron-nickel alloys obtained by unsteady electrolysis. It was found that the use of a unipolar pulse current leads to a significant increase in the crystallization overvoltage at the crystallization front at the moment of the pulse action, which affects the component composition of the coatings. The phase composition of the alloys formed at the cathode differs from that shown in the iron-nickel equilibrium diagram.